2023
DOI: 10.1590/s1677-5538.ibju.2023.0170
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral onlay ureteroplasty with buccal mucosa graft for complex proximal ureteral stricture

Abstract: Introduction: There is lack of papers dedicated to the laparoscopic buccal mucosa graft (BMG) ureteroplasty of the complex upper ureteral stricture. The aim of this study is to evaluate the results of laparoscopic BMG ureteroplasty in patients with complex proximal ureteral stricture. Material and methods: Twenty-four patients underwent laparoscopic ventral onlay BMG ureteroplasty for long or recurrent proximal ureteral stricture not amenable to uretero-ureteral anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…В настоящее время лоскут из слизистой оболочки щеки активно используют для замещения длинных стриктур уретры. Постепенно некоторые клиники набирают опыт пластики протяженных дефектов мочеточника этим трансплантатом [8][9][10][11][12][13][14]. Важное значение имеет возможность изучения приживляемости БГ, определения сроков его окончательной васкуляризации, а также патоморфологических изменений, происходящих с эпителием лоскута, который использовался для уретеропластики.…”
Section: Discussionunclassified
“…В настоящее время лоскут из слизистой оболочки щеки активно используют для замещения длинных стриктур уретры. Постепенно некоторые клиники набирают опыт пластики протяженных дефектов мочеточника этим трансплантатом [8][9][10][11][12][13][14]. Важное значение имеет возможность изучения приживляемости БГ, определения сроков его окончательной васкуляризации, а также патоморфологических изменений, происходящих с эпителием лоскута, который использовался для уретеропластики.…”
Section: Discussionunclassified
“…Those located at the proximal ureter can be treated by a pyeloplasty ( 4 ). The ureteric strictures in the mid-ureter are the ones that pose a greater challenge for the urologist because a ureteral substitution is needed, either using a segment of the intestine or a buccal mucosa graft ( 5 , 6 ). Our main objective is to present the management and results at 36 months of a patient with a right mid-ureter stricture.…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Guliev and collegues from Russia performed on page 619 ( 7 ) an nice study about the laparoscopic ventral onlay ureteroplasty with buccal mucosa graft for complex proximal ureteral stricture and concluded that patients with proximal ureteral strictures could be effectively treated by laparoscopic ventral onlay ureteroplasty with a buccal mucosa graft.…”
mentioning
confidence: 99%